2017
DOI: 10.1161/circulationaha.116.026778
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Obesity and Underweight Status on Perioperative Outcomes of Congenital Heart Operations in Children, Adolescents, and Young Adults

Abstract: Background Extreme BMI (either very high or very low) has been associated with increased risk of adverse perioperative outcome in adults undergoing cardiac surgery. The effect of body-mass index (BMI) on perioperative outcomes in congenital heart disease patients has not been evaluated. Methods A multicenter retrospective cohort study was performed studying patients 10–35 years undergoing a congenital heart disease operation in the Society of Thoracic Surgeons Congenital Heart Surgery Database between 1/1/20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 53 publications
1
22
2
Order By: Relevance
“…While we found an association between underweight infants and a longer LOS as seen in other studies of underweight pediatric patients, we did not find this association in underweight children but did find an association with excess weight 32,33 . We found that overweight children had a shorter LOS, while obese children had a longer LOS than their normal‐weight counterparts.…”
Section: Discussioncontrasting
confidence: 50%
“…While we found an association between underweight infants and a longer LOS as seen in other studies of underweight pediatric patients, we did not find this association in underweight children but did find an association with excess weight 32,33 . We found that overweight children had a shorter LOS, while obese children had a longer LOS than their normal‐weight counterparts.…”
Section: Discussioncontrasting
confidence: 50%
“…Some other studies inferred that the obesity rates in children with CHD are likely much higher than the general population . Data analyzed in previous studies are over 10 years old; while it is known in the general population that the risk of obesity has increased in the last 10 years with the “obesity epidemic,” previous studies on patients with CHD have not defined the timing of overweight and obesity onset which can be critical for preventive efforts.…”
Section: Introductionmentioning
confidence: 99%
“…the last 10 years with the "obesity epidemic," 6,10 previous studies on patients with CHD have not defined the timing of overweight and obesity onset which can be critical for preventive efforts.…”
mentioning
confidence: 99%
“…9 On the other hand, being underweight is an established predictor of morbidity and mortality in acquired heart failure 15 and may be an equally important marker of increased health risk as overweight/obesity in specific CHD populations. 17 In the current study, we sought to investigate the status of BMI in different ACHD lesions and its association with different factors such as age, exercise capacity, and ventricular function in order to prevent and manage subsequent detrimental comorbidity risks. 5,16 To the best of our knowledge, the prevalence of underweight in ACHD patients has not been described previously, although a recent study showed high prevalence of underweight in CHD patients.…”
mentioning
confidence: 99%
“…5,16 To the best of our knowledge, the prevalence of underweight in ACHD patients has not been described previously, although a recent study showed high prevalence of underweight in CHD patients. 17 In the current study, we sought to investigate the status of BMI in different ACHD lesions and its association with different factors such as age, exercise capacity, and ventricular function in order to prevent and manage subsequent detrimental comorbidity risks. that could affect body habitus and those with Eisenmenger physiology, mental retardation, and severe psychological disorders were excluded from the study.…”
mentioning
confidence: 99%